Health Professionals' Attitude Toward the Use of Social Media for COVID-19 Related Information in Northwest Ethiopia: A Cross-Sectional Study - Masresha Derese Tegegne; Berhanu Fikadie Endehabtu; Habtamu Alganeh Guadie; Tesfahun Melese Yilma (Frontiers Media S.A., 2022)
BackgroundSocial media platform is one way to share online information regarding pandemic prevention. However, there is no study regarding the attitude of health professionals toward social media use for the COVID-19-related information. This study aimed to assess health professionals' attitudes toward using social media for COVID-19-related information.MethodsAn institution-based cross-sectional study was conducted among 355 health professionals in Bahir Dar city public health centers, Northwest Ethiopia. A pretested self-administered questionnaire was used to collect the data. The data were entered by EPI-data version 4.6 and analyzed using SPSS version 23 software. Descriptive statistics, bivariable, and multivariable logistic regression analysis were used to describe respondents' attitudes toward using social media for COVID-19 information and identify associated factors. An adjusted odds ratio (OR) and a p-value with a 95% CI were calculated to measure the strength of the association and assess statistical significance.ResultOut of 341 participants, about 73% of the participants had a good attitude toward the use of social media for COVID-19 information. Age < 24 [adjusted odds ratio (AOR) = 3.74, 95% CI: (1.53-9.13)] and age group 25-34 years [AOR = 2.25, 95% CI: (1.04-4.86)], computer training [AOR = 2.03, 95% CI: (1.03-4.00)], usefulness of social media [AOR = 3.25, 95% CI: (1.58-6.67)], and trustworthiness [AOR = 3.57, 95% CI: (1.93-6.60)] were enabling factors for attitude toward the use of social media for COVID-19 related information.ConclusionHealth professionals had a moderate attitude toward using social media for accessing COVID-19-related information. This implies that after considering positive attitude predictors, such as providing basic computer training, emphasizing the usefulness of social media, and building trusted social media pages, social media platforms can be used as a source of COVID-19-related information for health professionals.